Kissing in the Hebrew Bible: The Body Makes the Bond - Mirguet, Françoise (Biblical interpretation, 2025)
This article explores the role of kissing (root nashaq) in the cultural imagination of the Hebrew Bible. Informed by current research in neuroscience and the history of emotions, it problematizes the prevailing assumption in biblical scholarship that kissing is a manifestation of love and affection. Biblical texts never explicitly present kissing as the expression of an emotion. The article examines the movements, body parts, and sensory experiences involved in kissing. As a full-body movement and close contact that heighten the sensory perception of the other, it is usually a unilateral practice that enacts social roles and shapes bonds. In biblical imaginations of kissing, cultural attention generally focuses on what bodies do and how they shape social dynamics. In line with the biblical construction of emotions, typically understood as embodied and social practices, kissing should not automatically be viewed as a manifestation of an internal state.